2019
DOI: 10.1177/0894439319826904
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Respondents’ Attitudes Toward Web Paradata Use

Abstract: The collection and use of paradata is gaining in importance, especially in web surveys. From a research ethics’ perspective, respondents should be asked for their consent to the collection and use of web paradata. In this context, a positive attitude toward paradata use has been deemed to be a prerequisite for respondents’ willingness to share their paradata. The present study aimed to identify factors affecting respondents’ attitudes toward paradata use. Our findings revealed that adequately informing survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…To ascertain the effect of consent structure on willingness to participate and consent to data analysis, we computed either linear regression models with the numeric response as dependent variable, or logistic models with a dichotomized dependent variable, split mid-scale (as in Kunz and Gummer 2019). In either case, the contrast-coded predictors ically, respondents were asked to imagine another unrelated study where they could separately indicate their willingness to participate in mouse-tracking.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To ascertain the effect of consent structure on willingness to participate and consent to data analysis, we computed either linear regression models with the numeric response as dependent variable, or logistic models with a dichotomized dependent variable, split mid-scale (as in Kunz and Gummer 2019). In either case, the contrast-coded predictors ically, respondents were asked to imagine another unrelated study where they could separately indicate their willingness to participate in mouse-tracking.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to substantial degrees of freedom, for example concerning the question whether to make mouse-tracking a mandatory part of the overall study consent, or an additional opt-in. Similarly, researchers may want to explain and justify the need for mouse-tracking: If survey designers can communicate their reasoning and the benefits of mouse-tracking, respondents may decide whether they consider them commensurate to the potential privacy invasion, which could lead to overall higher consent rates (as in Kunz and Gummer 2019). This line of reasoning is formalized in Contextual Integrity theory (Nissenbaum 2011(Nissenbaum , 2004(Nissenbaum , 2018, which states that privacy violations occur when context-specific informational norms are broken.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we know from related research on linking survey data to administrative records that opt-out consent procedures can lead to higher consent rates compared with opt-in procedures (Sakshaug et al, 2016). With regard to other design characteristics, previous studies have shown that a clear description of the type of web paradata collected and the purposes for which they are used generally helps to promote a positive attitude toward the collection and use of web paradata (Couper & Singer, 2013; Kunz & Gummer, 2019). Moreover, asking for web paradata consent at the beginning of the questionnaire rather than at the end seems to build trust, and therefore, results in higher consent rates (Couper & Singer, 2013; Sattelberger, 2015).…”
Section: Introductionmentioning
confidence: 99%